Paola Torres: “One thing that can describe me is activism”: Interview with the female doctor and cordelist who uses popular culture to teach about cancer. (Revista Internacional de Folkcomunicação, 2024)
Interview with doctor, professor of Medicine and cordelist Paola Torres, who uses cordel literature to teach students, healthcare professionals and patients about cancer.